1988
DOI: 10.1007/bf00412682
|View full text |Cite
|
Sign up to set email alerts
|

Fc? receptors on keratinocytes in psoriasis

Abstract: Epidermis in cryostat sections of skin biopsy specimens from patients with psoriasis and from healthy individuals bound bovine erythrocytes (E) sensitized with rabbit IgG antibodies (A)(EA). No binding occurred using E or E sensitized with IgM or F(ab')2 fragments of IgG. The binding of EA was inhibited by human IgG and by Fc fragments of IgG, whereas human IgA, IgM, albumin, and F(ab)2 fragments of IgG did not inhibit the binding, indicating the presence of receptors for the Fc part of IgG (FcR). EA bound mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…According to the histological and clinical picture of the disease, EBA belongs to the epidermolysis bullosa group of diseases (8, 151, and the term ))mechanobullous dermatosescc has been proposed (2, 13). The case presented fulfils the clinical and histological criteria for the diagnosis for EBA as discussed elsewere (9). The electron microscopic findings eith blister formation below the lamina densa in bo,th skin lesions and friction blisters are in keeping with electron microscopic studies of skin lesions in a few reported cases of EBA ( I , I 3, 1 5 , 17).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…According to the histological and clinical picture of the disease, EBA belongs to the epidermolysis bullosa group of diseases (8, 151, and the term ))mechanobullous dermatosescc has been proposed (2, 13). The case presented fulfils the clinical and histological criteria for the diagnosis for EBA as discussed elsewere (9). The electron microscopic findings eith blister formation below the lamina densa in bo,th skin lesions and friction blisters are in keeping with electron microscopic studies of skin lesions in a few reported cases of EBA ( I , I 3, 1 5 , 17).…”
Section: Discussionsupporting
confidence: 75%
“…Initially he was treated with prednisone and azathioprine without improvement. From February I978 he was successfully treated with gold sodium thiomalate, reaching a total dose of 1000 mg. A detailed description of the clinical course is given elsewhere (9). Hisropathological Studies.…”
Section: Case Reportmentioning
confidence: 99%
“…Recently, we demonstrated FcR on keratinocytes in normal and psoriatic skin [13]. Enhanced FcR activity by keratinocytes was found in psoriatic skin lesions compared with normal skin and strongest above areas with mononuclear cell infiltrates.…”
Section: Discussionmentioning
confidence: 91%
“…The presence of IFN-e in the basal keratinocytes and in epidermal dendritic cells may therefore influence the HLA-DR expression induced by IFN-7. According to Yasutaka et al [34] crosslinking of FcR on various cell lines in vitro inhibited the ability of IFN-7 to induce HLA-DR. An in vivo cross linking of FcR on keratinocytes [13] may therefore be another explanation for the reduced expression of HLA-DR on keratinocytes in psoriatic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation